IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI UNTUK MEMENUHI KEBUTUHAN BELAJAR ANAK DI TAMAN KANAK-KANAK KELAS B - Milawati; Darmiyati; Aslamiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Differentiated instruction is a crucial approach in early childhood education, particularly in Kindergarten B, as it accommodates the diversity of students’ abilities, interests, and learning styles. This study aims to review the implementation of differentiated instruction in Kindergarten B through a literature analysis of national and international research published between 2015 and 2025. The method employed is a descriptive literature review using a qualitative approach, analyzing 20 verified academic sources, including publications by lecturers from Universitas Lambung Mangkurat and other higher education institutions. The findings indicate that differentiated instruction positively contributes to enhancing children’s learning motivation, creativity, and independence. Furthermore, this approach enables teachers to develop more flexible and child-centered learning strategies. However, several challenges arise in its implementation, such as limited instructional time, insufficient teacher skills in conducting initial assessments, and high student–teacher ratios. To address these obstacles, continuous professional development for early childhood educators and supportive policies that enable the implementation of adaptive and responsive curricula are needed. This review is expected to serve as a reference for developing inclusive and individualized learning practices that align with the diverse needs of early learners.